Miguelina Aurora Acosta Cárdenas: a chapter in Peruvian legal feminism - Flores Heredia, Gladys (2023)
This article seeks to explain some of the reflections of Miguelina Aurora Acosta Cárdenas (1887-1933) on the legal status of women. To this end, we divide the text into two parts. The first part describes the process of Miguelina’s intellectual formation, and the second part comments on and explains the main ideas that the author developed in articles published in journals of the time and in her university theses on the necessary modern orientation that the rules and institutions that regulate the rights and opportunities of men and women should have.